Enhancing ambient and elevated temperature performance of hypoeutectic Al–Ce cast alloys by Al3(Sc,Zr) precipitate - Mohammed, Abid A.; Chankitmunkong, Suwaree; Wang, Shihao; Eskin, Dmitry G.; Patakham, Ussadawut; Limmaneevichitr, Chaowalit; Pandee, Phromphong (My University, 2024)
This study explored the consequences of incorporating Sc and Zr into hypoeutectic Al–9Ce cast alloys, specifically investigating their influence on microstructure and mechanical properties. The findings demonstrated the significant reduction in the grain size of the Al–9Ce alloy while successfully maintaining the distinctive shape of the eutectic Al11Ce3 phase through the incorporation of Sc and Zr additions. During aging treatments, Al3(Sc,Zr) coherent precipitates formed both at the interface between the α-Al and Al11Ce3 phases and within the α-Al matrix. Remarkably, this led to optimal hardness achieved within a short duration of 3 h at 350 °C. Peak-aged quaternary Al–9Ce–xSc–yZr alloys showed significantly better tensile strength than the binary Al–Ce alloy at both ambient and elevated temperatures. Overall, the study underscored promising prospects of Al–Ce–Sc–Zr alloys for use in high-temperature applications, as they exhibited enhanced mechanical properties.
Keywords: Al11Ce3; Al3(Sc,Zr); Aluminum-cerium alloys; Al–Ce–Sc–Zr; Casting